Developing a model of industry-based practicum learning - Bambang Sudarsono; Thomas Sukardi (Jurnal Pendidikan Vokasi, 2017)
The study was to: (1) produce a practicum learning model that might be applied by the lecturers of Automotive Engineering Education Program as the center of Light Vehicle Engineering (LVE) Study Program prospective teachers in the vocational high schools (VHS); (2) identify the automotive industry-oriented competence aspects in practicum learning needed by the LVE Study Program prospective teachers in the VHS; (3) identify the degree of implementatibility of the practicum learning model that had been developed for the LVE Study program prospective teachers in the VHS; and (4) identify the effectiveness degree of the practicum learning model that had been developed for the LVE Study Program prospective teachers in the VHS. The model development in the study referred to the research and development model proposed by Richey and Klein. The research subjects were the students of Automotive Engineering Education Study Program Muhammadiyah University Purworejo. Then, the research objects were Toyota Magelang Company, the Daihatsu Armada Company and the Ultratune Company Gadjah Mada University. The results of the study show that: (1) the competency aspects developed in the P2BI Model for the students who refer the LVE Study Program prospective teachers include the affective aspect, the cognitive aspect and the psychomotor aspect; (2) the improvement of the affective, the cognitive and the psychomotor aspect has met the "Very Good" criteria; (3) the students' activities in the implementation of the P2BI Model Stages have been very good; and (4) the students' responses toward the P2BI Learning Model have been very positive.Keywords: learning model, practicum learning, LVE Study Program prospective teachers PENGEMBANGAN MODEL PEMBELAJARAN PRAKTIK BERBASIS INDUSTRIAbstrakTujuan penelitian ini adalah untuk: (1) menghasilkan model pembelajaran praktik yang dapat diterapkan oleh dosen pendidikan teknik otomotif sebagai penghasil calon guru SMK Program Keahlian Teknik Otomotif (PKTO), dan (2) mengetahui aspek-aspek kompetensi pada pembelajaran praktik yang dibutuhkan calon guru SMK PKTO. Model pengembangan dalam penelitian ini mengacu model research and development dari Richey and Klein. Subjek penelitian adalah mahasiswa Program Studi Pendidikan Teknik Otomotif Universitas Muhammadiyah Purworejo. Objek penelitian di PT. Toyota Magelang, PT. Daihastu Armada dan PT. Ultratune UGM. Hasil penelitian ini adalah sebagai berikut. (1) Aspek-aspek kompetensi yang dikembangkan pada model P2BI bagi mahasiswa calon guru SMK PKTO adalah aspek sikap,aspek pengetahuan dan aspek ketrampilan. (2) Peningkatan aspek sikap, pengetahuan dan ketrampilan dengan kriteria sangat baik. (3) Aktivitas mahasiswa dalam pelaksanaan tahapan-tahapan model P2BI sangat baik dan (4) Tanggapan mahasiswa terhadap model pembelajaran P2BI sangat positif.Kata Kunci: model pembelajaran,pembelajaran praktik, calon guru SMK PKTO